2021
DOI: 10.1007/s00268-021-06264-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Neutrophil‐to‐Lymphocyte Ratio may Predict Postoperative Pneumonia in Stage I–III Gastric Cancer Patients After Curative Gastrectomy: A Retrospective Study

Abstract: Background: Several studies have demonstrated that diverse systemic in ammatory-based prognostic parameters predict poor prognosis in patients with gastric cancer. However, few studies focused on the relationships between postoperative complications and systemic in ammatory-based prognostic parameters after curative gastrectomy. We investigated the relationships between postoperative complications and these parameters to identify parameter-speci c postoperative complications, and assessed the clinical utility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…[39][40][41] Recent studies also showed that preoperative inflammatory markers can effectively predict postoperative complications such as pneumonia and anastomotic leakage in gastric cancer patients after gastrectomy. 42,43 Moreover, a scoring system combined multifactors including inflammatory and nutritional showed promising role in predicting prognosis in gastric cancer. Hirahara et al found that the systemic immune-inflammation index (SII), integrated by peripheral lymphocyte, neutrophil, and platelet counts, was an independent prognostic factor for overall survival in gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] Recent studies also showed that preoperative inflammatory markers can effectively predict postoperative complications such as pneumonia and anastomotic leakage in gastric cancer patients after gastrectomy. 42,43 Moreover, a scoring system combined multifactors including inflammatory and nutritional showed promising role in predicting prognosis in gastric cancer. Hirahara et al found that the systemic immune-inflammation index (SII), integrated by peripheral lymphocyte, neutrophil, and platelet counts, was an independent prognostic factor for overall survival in gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are well-known systemic inflammatory variables related to the prognosis of colorectal, gastric, and pancreatic cancer [ 17 19 ]. Some recent studies suggest that systemic inflammatory variables may be useful for the prediction of postoperative complications in patients with various cancers [ 20 22 ]. However, few studies have focused on the relationships between systemic inflammatory variables and postoperative complications in patients with acute appendicitis.…”
Section: Introductionmentioning
confidence: 99%